IMMUN RESPONSES IN COVID-19 - Bülent Çakal (İstanbul Tıp Fakültesi Dergisi)
The Coronavirus disease 19 (COVID-19) pandemic, which is the etiological agent of a severe acute respiratory syndrome-associated coronavirus (SARS-CoV-2), has influenced the whole world with the current and possible results. COVID-19 has very unique virological, clinical and immunological characteristics. In COVID19, immune responses can vary widely, ranging from responses that allow control of the infection to pulmonary thrombosis characterized by sudden and rapidly developing intense inflammation and storm of cytokenemia. This review aims to examine scientific data about immunopathogenesis of COVID-19